Impact of in-band crosstalk in an optical network based on multi-degree CDC ROADMs - Sequeira, Diogo Gonçalo (2018)
he most common optical networks nodes are known as reconfigurable optical add/drop multiplexers (ROADMs). The architecture and components of these nodes have evolved over the time to become more flexible and dynamic. Particularly, the wavelength add/drop structures of these nodes have become more complex and with new features such as colorless, directionless and contentionless (CDC). One of the main limitations of the optical networks physical layer, the in-band crosstalk, is mainly due to the imperfect isolation of the components inside these nodes. This crosstalk is enhanced, when an optical signal traverses a cascade of ROADM nodes. In this work, the impact of in-band crosstalk, optical filtering and amplified spontaneous emission (ASE) noise on the performance of an optical communication network based on a cascade of CDC ROADMs with coherent detection and the modulation format quadrature phase-shift keying with polarization-division multiplexing (PDM-QPSK) at 100-Gb/s is studied through Monte-Carlo simulation. Two architectures, broadcast and select (B&S) and route and select (R&S), and two possible implementations for the add/drop structures, the multicast switches (MCSs) and the wavelength selective switches (WSSs), were considered. The degradation of the optical communication network performance due to in-band crosstalk is assessed through the optical-signal-to-noise ratio (OSNR) calculation. In particular, an OSNR penalty of 1 dB due to in-band crosstalk is observed when the signal passes through a cascade of 19 CDC ROADMs with 16-degree, based on a R&S architecture and with add/drop structures implemented with WSSs